Sickle cell retinopathy: diagnosis and treatment - Bonanomi,Maria Teresa Brizzi Chizzotti (2013)
Hemoglobinopathies are a group of inherited disorders characterized by quantitative or qualitative malformations of hemoglobin (Hb). Some of these diseases present vaso-occlusive phenomena that are responsible for high morbidity in clinical and/or ophthalmologic terms. Diagnosis of hemoglobinopathies is performed exclusively through hemoglobin electrophoresis. From the ophthalmologic perspective, the most important representative of this group of diseases is sickle cell retinopathy, which presents a wide spectrum of fundus manifestations and may even lead to irreversible vision loss if not properly diagnosed and treated. The aim of this review is to present the classification of sickle cell retinopathy and to describe current management and future perspectives for its treatment, taking into consideration the clinical management of these patients.